2016
DOI: 10.1007/s00268-016-3409-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Pneumonia and Postoperative Venous Thrombosis: A Cohort Study of 427,656 Patients Undergoing Major General Surgery

Abstract: A large, multicenter database of surgical patients showed that preoperative pneumonia may increase risk for developing venous thrombosis. This adds to our understanding of risk factors for venous thrombosis and suggests a potential benefit of diagnosing preoperative pneumonia in patients undergoing major general surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Generally, the type of surgery performed was decided according to the protocols of our institution, summarized as follows: 18 and activities of daily living [ADL] score) 19 ; (iii) laboratory test results (e.g. for white blood cell count and C-reactive protein); and (iv) comorbidities and other histories.…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the type of surgery performed was decided according to the protocols of our institution, summarized as follows: 18 and activities of daily living [ADL] score) 19 ; (iii) laboratory test results (e.g. for white blood cell count and C-reactive protein); and (iv) comorbidities and other histories.…”
Section: Surgerymentioning
confidence: 99%
“…Sarah et al reported an increase in the postoperative mortality rate in patients undergoing orthopaedic, thoracic, and vascular surgeries with preoperative pneumonia 18 . In a large multicenter retrospective cohort study that included 427,656 patients admitted for major general surgeries, preoperative pneumonia was identified as a risk factor of venous thrombosis after surgery 19 . Although preoperative pneumonia was related to poor prognosis after surgery, many patients were still undergoing surgeries when antibiotic therapy was initiated; this may be influenced by the timing of the specific surgery 18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative pneumonia is associated with postoperative complications following a broad range of surgeries. 13,14 Here, we showed that pneumonia was associated with a 6-fold increase in postoperative acute respiratory failure following sinus surgery. Preoperative optimization and treatment of pneumonia should continue and elective surgery be delayed until pneumonia resolves.…”
Section: Discussionmentioning
confidence: 91%
“…First, the prevalence of hospitalization with infection 14, 30, 42, and 90-days prior to VTE was compared to the corresponding time periods exactly 1 and 2 years prior to the VTE event. Conditional logistic regression was used to estimate odds ratios (OR) of VTE and 95% confidence intervals (CIs) for each time period (14,30,42, and 90 days). We controlled for the number of hospitalizations in the 9 months preceding each case or control period to account for potential decline in overall health status due to age and immobility associated with hospitalization.…”
Section: Discussionmentioning
confidence: 99%